Uji Aktivitas Antidiare Ekstrak Daun Srikaya (Annona squamosa L.) Pada Mencit Putih Jantan (Mus musculus) dengan Metode Transit Intestinal - Evanisia More; Veronika U. Banggut; Yohanes D. P. A. Embu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Diarrhea is a gastrointestinal disorder characterized by an abnormal increase in the frequency of bowel movements, more than three times a day, accompanied by a change in stool consistency to a more liquid state, with or without blood or mucus. Srikaya leaves (Annona squamosa L.) are one of the medicinal plants used as an antidiarrheal based on their secondary metabolite content. This study aims to determine the antidiarrheal activity of srikaya leaf extract (Annona squamosa L.) and to find the most optimal dose as an antidiarrheal by observing intestinal motility. The method used is the intestinal transit method, where the parameter observed is the length of the intestine passed by the marker compared to the total length of the intestine. A total of 25 male white mice were divided into 5 groups, each consisting of 5 mice, namely the negative control group given 0,5% Na-CMC, the positive control group given loperamide HCl, and test groups I, II, and III given srikaya leaf extract at doses of 200 mg/kgBW, 400 mg/kgBW, and 600 mg/kgBW, respectively. The data obtained were analyzed using One Way ANOVA. The results showed that srikaya leaf extract (Annona squamosa L.) had antidiarrheal activity with the most optimal dose being 600 mg/KgBW. The antimotility percentage was 54,76%.